Peculiarities of somatic pathology in children with cerebral palsy (literature review) - S.L. Nyankovsky; A.I. Pushnyk; O.V. Kuksenko (Zaslavsky O.Yu., 2017)
Cerebral palsy remains one of the most topical problems of pediatric neurology and causes of childhood disability. This term includes group of syndromes that result from violations of or damage to the central nervous system. The incidence of cerebral palsy does not tend to decrease due to such factors, as the improvement of nursing methods and reduced mortality of prematurely born babies and infants with extremely low birth weight. The most common forms of cerebral palsy are spastic forms: spastic diplegia, spastic hemiparesis, double hemiplegia. Their share is 80-85 % of all cases of cerebral palsy. According to available data, children with cerebral palsy suffer from impairments of somatic health, physical development and regulatory mechanisms. The rehabilitation effectiveness of such children often depends on their rehabilitation potential, which depends on concomitant somatic pathology and functional disorders. It was found that anemia had a 3.6 times higher rate in children with spastic forms of cerebral palsy than in their healthy peers, rachitis - 2.9 times more higher, malnutrition - 12.8 times more higher. Among children with cerebral palsy, a group of frequently and chronically ill children included 5.6 times more children than comparison group. Chronic adenoiditis, rhinitis, otitis in children with cerebral palsy were diagnosed 6.5 times more often than in the comparison group. Cerebral palsy is a complicated, multicomponent problem, in the development of pathogenic mechanisms of which, somatic pathology plays a prominent role that suggests the need for multidisciplinary approach to the treatment, involving medical experts of different specialties.